DIGITAL COMMUNICATION AND BELONGING: HOW FIRST-YEAR UNIVERSITY STUDENTS NAVIGATE ONLINE AND OFFLINE SOCIAL INTEGRATION - Aldianto, A; Kausch II, Christopher (Jurnal Pendidikan Ilmu Sosial, 2025)
The rapid digitalization of higher education has transformed how first-year university students form social connections and construct a sense of belonging. This research explores how Indonesian and American first-year students navigate belonging, authenticity, and identity through online and offline communication. Drawing on Theory of Student Integration, Social Information Processing Theory,  and Social Identity Theory, the research investigates how digital and physical spaces intersect to shape students’ adaptation to university life. Using a qualitative exploratory design, fifteen first-year students, eight from a mid-sized university in Surabaya, Indonesia, and seven from Rochester, United States, participated in semi-structured interviews and online ethnographic observations. Thematic analysis revealed three key findings. First, digital communication serves as a social bridge, reducing anxiety and facilitating early peer connections, yet emotional depth arises mainly through face-to-face interactions. Second, students experience an authenticity paradox, as online engagement enables inclusion but also creates performance pressure and emotional fatigue. Third, digital spaces support identity negotiation and linguistic creativity, particularly through translanguaging and cultural adaptation. These findings suggest that belonging is a hybrid communicative process, co-constructed through both mediated and embodied interactions. The study concludes that universities should implement hybrid communitybuilding programs and communication literacy initiatives to foster authentic, inclusive belonging in the digital age.